Expanding Access and Enhancing the Economic Benefits of Education in the Maldives : Challenges and Prospects - World Bank (Washington, DC, 2014)
Human capital is the central determinant of economic well-being and social advancement in the modern global economy. The key characteristic that distinguishes between advanced economies, middle-income economies and low-income economies is the knowledge content of their economic activities and production processes. Industry, agriculture and especially services have become increasingly knowledge and skill intensive in recent years. Further, the dominance of knowledge and skills is increasing at an accelerating rate. Among advanced economies, for instance, the education levels of their populations is the single most important factor determining their economic performance [Hanushek and Welch (2006), Hanushek and Woessmann (2008)]. Among middle-income and low-income countries, too, economies that have high education attainment enjoy considerable welfare gains [Fasih (2008), Patrinos and Psacharopoulos (2011)]. Human resource development is particularly important for the economic development of small states [Martin and Bray (2011)]. Education also produces a variety of social benefits. These include healthier and better nourished families and children; the creation of the enlightened citizenry needed for a modern liberal democracy; and the promotion of social mobility [OECD (2012)]. This paper offers an overview of the general education system and the current status of access and participation in the Maldives. This is followed by a discussion of the economic and social benefits of investment in education. The paper concludes by discussing options to expand access and participation at education levels where the Maldives lags behind other comparable small island economies.